Effect of kinesio taping in combination with vibration treatment on college students’ delayed-onset muscle soreness - Que, Ning (Frontiers in Physiology, 2023)
Background: Kinesio taping (KT) and vibration treatment (VT) can alleviate delayed-onset muscle soreness (DOMS) to some extent. However, the literature reports on the difference between the two treatments, and whether a joint intervention (JI) works better than single treatments remains unknown. Objective: This study compares the effects of KT, VT and JI on DOMS in college students. Methods: A total of 88 college students were randomly divided into the KT (KTG, n = 21), VT (VTG, n = 22), JI (JIG, n = 23) and control (CG, n = 22) groups. All subjects underwent DOMS moulding. The baseline; immediate and 24, 48 and 72 h visual analogue scale (VAS) scores and knee extensor maximum isometric voluntary contraction (MIVC) were determined. Results: The intergroup comparison showed the following results. 1) The VAS scores of the four groups peaked at 24 h and gradually decreased. The immediate, 24 h and 48 h VAS scores followed the order: JIG > KTG and VTG > CG. The 72 h VAS score followed the order: KTG < VTG < JIG < CG. 2) The knee extension MIVC in the four groups was lowest at 24 h and then gradually increased. JIG had larger immediate MIVC than CG. KTG, VTG and JIG had larger 24 h MIVC than CG. JIG had larger 48 h MIVC than KTG and CG. Conclusion: KT and VT can reduce muscle pain and strength loss caused by DOMS to varying degrees. VT is better than KT in improving pain. The combined intervention worked better than single interventions.